2012
DOI: 10.1093/brain/aws289
|View full text |Cite
|
Sign up to set email alerts
|

Protection of primary neurons and mouse brain from Alzheimer's pathology by molecular tweezers

Abstract: Alzheimer's disease is a devastating cureless neurodegenerative disorder affecting >35 million people worldwide. The disease is caused by toxic oligomers and aggregates of amyloid β protein and the microtubule-associated protein tau. Recently, the Lys-specific molecular tweezer CLR01 has been shown to inhibit aggregation and toxicity of multiple amyloidogenic proteins, including amyloid β protein and tau, by disrupting key interactions involved in the assembly process. Following up on these encouraging finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
151
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(163 citation statements)
references
References 61 publications
10
151
1
1
Order By: Relevance
“…However, this was found not Lys residues with micromolar affinity, which is relatively weak but has been found to be sufficient for modulating the assembly and inhibit the toxicity of multiple amyloidogenic proteins without causing toxicity in cell culture unless substantially higher concentrations were used [69]. These data are consistent with in vitro enzyme inhibition studies, which required MT concentrations at least an order of magnitude higher than those needed for inhibition of amyloidogenic proteins [68,70] and with data showing beneficial effects with no associated toxicity in animal models [71,72].…”
supporting
confidence: 73%
See 3 more Smart Citations
“…However, this was found not Lys residues with micromolar affinity, which is relatively weak but has been found to be sufficient for modulating the assembly and inhibit the toxicity of multiple amyloidogenic proteins without causing toxicity in cell culture unless substantially higher concentrations were used [69]. These data are consistent with in vitro enzyme inhibition studies, which required MT concentrations at least an order of magnitude higher than those needed for inhibition of amyloidogenic proteins [68,70] and with data showing beneficial effects with no associated toxicity in animal models [71,72].…”
supporting
confidence: 73%
“…In vitro studies of CLR01 inhibition of five major CYP enzymes showed IC 50 values of 1.5 μM for 2C19, 1.7 μM for 3A4, 2.2 μM for 2C9, 3.6 μM for 2D6, and >20 μM for 1A2 [71]. Inhibitory potencies are thought to have an increased risk for drug-drug interaction complications if the IC 50 is <1 μM [206], which was not found for CLR01 with any of the 5 isoforms studied.…”
Section: Effects On Ttr Toxicity In Vivomentioning
confidence: 90%
See 2 more Smart Citations
“…2a), disrupted in vitro the aggregation and toxicity of multiple disease-related proteins, such as amyloid β-protein (Aβ), tau and α-synuclein at equimolar or sub-equimolar concentration ratios (14), whereas disruption of tubulin polymerization required ~55-fold excess of CLR01 (15) and inhibition of enzymatic activity, e.g., of alcohol dehydrogenase, required ~850-fold excess CLR01 (16). In agreement with these observations, in vivo CLR01 suppressed α-synuclein aggregation in neurons and rescued the phenotype and survival of zebrafish embryos (17), cleared existing Aβ and tau aggregates in the brain of Alzheimer's disease transgenic mice, and decreased transthyretin aggregation in a mouse model of familial amyloidotic polyneuropathy, without any side effects (17)(18)(19). Moreover, CLR01 was found to have a high safety margin in mice (15), supporting its selective action as an inhibitor of abnormal protein aggregation.…”
Section: Introductionsupporting
confidence: 66%